Euclid’s Elements in Latin, 1482–1703: vocabulary and classiﬁcation - Wardhaugh, B (Société Mathématique de France, 2024)
This paper attempts an improved classification of the Latin texts of the Elements printed between 1482 and 1703. It uses primarily a comparison of the 114 terms defined within the text, supplemented by a comparison of the number of definitions included in each book and spot-check comparison of portions of the text and diagrams. The result is a classification into fourteen families. The process of classification permits some reflections on the degree to which the Latin Euclidean vocabulary stabilized during this period, and on the practices of the editors of these versions of the text, which prove to have been in a high proportion of cases eclectic, with definitions, enunciations, proofs and diagrams frequently based on different sources or modified idiosyncratically, even in cases where a specific model was named in the paratext.